2017
DOI: 10.1007/s10900-017-0353-4
|View full text |Cite
|
Sign up to set email alerts
|

Community Violence Exposure and Risk Taking Behaviors Among Black Emerging Adults: A Systematic Review

Abstract: Black emerging adults ages 18–29, particularly those residing in predominantly black urban communities, are at risk for community violence exposure (CVE). This potentially traumatic event may induce traumatic stress reactions for black emerging adults that contribute to their engagement in violence perpetration, substance use and/or sexual risk-taking behaviors as a way to cope with their experiences. To address these identified concerns and make recommendations for future research, this article identifies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 54 publications
(76 reference statements)
0
30
0
1
Order By: Relevance
“…Our findings extend existing research about the clustering of health risk behaviors 3,11 and indicate the importance of examining socio-environmental factors when addressing health risk behaviors among African Americans. 27 A prior cross-sectional study showed that neighborhood cohesion, instead of individual-level demographic correlates, is a crucial predictive factor for African Americans engaging in multiple health behaviors. 8 Our findings of ETV adds to such evidence with longitudinal data that violence in the neighborhood and other social environments may play an important role in shaping various health risk behaviors later in life among African Americans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings extend existing research about the clustering of health risk behaviors 3,11 and indicate the importance of examining socio-environmental factors when addressing health risk behaviors among African Americans. 27 A prior cross-sectional study showed that neighborhood cohesion, instead of individual-level demographic correlates, is a crucial predictive factor for African Americans engaging in multiple health behaviors. 8 Our findings of ETV adds to such evidence with longitudinal data that violence in the neighborhood and other social environments may play an important role in shaping various health risk behaviors later in life among African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased risk of maladjusted health behaviors from ETV, 27 including those examined in the current study, health promotion professionals must be mindful of the presence and consequences of ETV when developing and implementing chronic disease prevention and control programs in areas where community violence is a problem. Individuals who have experienced high levels of ETV may have difficulties with coping, social support, and access to resources to be physically active, eat right, and avoid harmful substance use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…成员的健康, 并且一系列研究指出它是导致不同阶 层之间健康差距的社会机制 [49,50] . 更多的暴力接触 与更严重的哮喘症状有关, 也与更大风险的心血管 疾病有关; 遭受暴力也与身体健康状况较差、残疾程 度高、慢性疼痛密切相关 [51,52] . 通过统计控制了个体 所经历的暴力事件后, 社会阶层与自我报告的健康 状况之间相关度降低 [53] .…”
Section: 个体所居住的社区提供了一个形成个体所经历 的各种社会风险的背景 社区暴力能显著影响社区unclassified